2005
DOI: 10.1016/j.febslet.2005.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human telomerase by oligonucleotide chimeras, composed of an antisense moiety and a chemically modified homo‐oligonucleotide

Abstract: Most tumor cells attain their immortality by reactivating telomerase. We report here the telomerase inhibitory potential of chimeric oligonucleotides composed of a 13mer antisense sequence targeting the telomerase RNA template region and a (s 4 dU) n moiety at its 3 0 or 5 0 -end. The increase of the thiolated chain length enhances the telomerase inhibitory potential, but decreases specificity, indicated by HIV reverse transcriptase inhibition. Chimeras with 5 0 (s 4 dU) n s were more potent inhibitors than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…A lot of reports have confirmed that antisense oligonucleotides can bind start location of mRNA translation inside cells, block translation of target RNA into target protein, and finally suppress cellular proliferation (14)(15)(16). However, antisense therapy is still restricted in application of clinical therapy because of two existing problems, such as rapid degradation by exonuclease or endonuclease and poor diffusion across the cell membrane (17)(18)(19). Although some methods, such as chemically modified oligonucleotides, oligonucleotides bound to virus and synthetic carriers, and small interfering RNA, have been explored to solve these problems (20,21), so far no optimal solution is established.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of reports have confirmed that antisense oligonucleotides can bind start location of mRNA translation inside cells, block translation of target RNA into target protein, and finally suppress cellular proliferation (14)(15)(16). However, antisense therapy is still restricted in application of clinical therapy because of two existing problems, such as rapid degradation by exonuclease or endonuclease and poor diffusion across the cell membrane (17)(18)(19). Although some methods, such as chemically modified oligonucleotides, oligonucleotides bound to virus and synthetic carriers, and small interfering RNA, have been explored to solve these problems (20,21), so far no optimal solution is established.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that UD29 is a mononucleotide, however, its deoxyoligonucleotide derivatives are also active biologically inhibiting the HIV entry and the telomerase enzyme [18,29,30]. Preliminary results on the activity of some other derivatives of the thiolated nucleotide and polynucleotide have also been reported [31].…”
Section: Discussionmentioning
confidence: 99%
“…3 In eukaryotic chromosomal DNA, telomeres are shortened each time a cell divides until they reach critical lengths that trigger cell death. 4 On the other hand, most cancer cells demonstrate high telomerase expression and the majority of human cancers prevent telomere erosion by telomerase. Telomerase activation by human telomerase reverse transcriptase (hTERT) has been described as a critical step during cancer progression, and the telomerase activation is also related to tumor cell radioresistance.…”
Section: Introductionmentioning
confidence: 99%